Characterizing Spatiotemporal Pattern of Vegetation Greenness Breakpoints on Tibetan Plateau Using GIMMS NDVI3g Dataset - Yong Ni; Yuke Zhou; Junfu Fan (IEEE Access, 2020)
Due to the harsh natural environment on the Tibetan Plateau (TP), its vegetation is sensitive to climate change. Therefore, it is essential to characterize long-term vegetation shifts for understanding of land surface processes across the TP. Gradual greening or browning growth in vegetation greenness is detectable while the alternating process between greening and browning, its timing, and type remain unclear. In this paper, breakpoint in time series of a satellite-derived vegetation index was detected at pixel-level during 1982-2012. The long-term growth procedure of vegetation was then characterized by combining the greening/browning trend for the two sub-periods, on each side of the breakpoint. The combinations of greening/browning status were classified into three categories (monotonic, interrupted and growth reversal). Possible causes for abrupt vegetation changes are discussed in the content of climate change and grassland management. Results show that breakpoints are temporally widely distributed and have significant spatial heterogeneity. About 21% (11%) of the vegetated area showed significant greening (browning) trends. Vegetation in central and eastern TP has tended to be greening. Browning trends were particularly evident in the southern and northeastern TP and were scarce in the west. About 32% of the vegetation was found to change significantly in this analysis. Greening trends occurred more often than browning trends and exhibited both a monotonic and an interrupted growing process. Trend reversal in vegetation was dominated by declining trends. Breakpoints in monotonic and interrupted trends were concentrated in some time points, but those with reversal trends were discretely distributed over time span. Among different ecosystem types, desert ecosystems presented the most significant greening trends, accounting for 53% of plant-covered desert. Conspicuous degraded trends were identified on alpine sparse vegetated area. Statistically, breakpoints in precipitation and air temperature are not consistent with those in vegetation greenness index. And grazing projects have not posed a significant effect on abrupt shifts in vegetation greenness.